Carbon content in different seagrass species in Andaman Coast of Thailand - Milica Stankovic; Janmanee Panyawai; Kamarudin Jansanit; Tipamat Upanoi; Anchana Prathep (Penerbit Universiti Kebangsaan Malaysia, 2017)
Seagrass meadows have one of the highest carbon sequestration and storage capacities than any other ecosystems. Carbon that is stored in the ecosystem is accumulated in the deposited sediment as well as in the living, above and below ground biomass, with a different rate of carbon sequestration and storage between the species. The objective of this research was to investigate carbon storage in the living plants and in the sediment among species of different size in tropical waters. The samples were collected from Phuket province, Thailand, in the high density monospecific patches of different size species (Enhalus acoroides as a big, Thalassia hemprhicii as a medium and Halophila ovalis as a small size species). Total carbon and carbon stored in above and below ground, was significantly different between the species (p<0.05), with the highest values in below ground parts of E. acoroides and T. hemprichii 238.10±85.07 and 134±21.55 g Dw m-2, respectively. Average organic carbon in the sediment was significantly different (p<0.05) as well, with E. acoroides having highest organic carbon content in the deeper layers of the sediment 1.14±0.25 % Corg, while the other two species had higher organic carbon in the top and medium layers of sediment. The results of this preliminary research propose that big size species have higher carbon content than smaller species, which reflects in higher sequestration rates of carbon from the ocean, thus reducing the ocean carbon budget. Moreover, it provides necessary information on size of the species which is the key for the future carbon storage studies in the region.